Light and electron microscopic studies on the duodenal mucosa in the badger - Ozdemir, D; Yilmaz, S; Dinc, G; Aydin, A; Atalar, O (Indian Veterinary Journal, 2004)
The badger (Meles meles) belongs to the Mustelidae family, which constitues a small group of the order Rodentia (Demirsoy, 1992). No work on the duodenum of the badger has been reported in the literature. The present work is the first to study light and electron microscopic picture of the duodenum of the badger.
Keywords: Brunners Glands